Negative electrode sheet and preparation method thereof and battery

By using graphite particles and cladding composite materials in the negative electrode material of lithium-ion batteries, the problems of low specific capacity and poor cycle stability of lithium-ion batteries are solved, and higher lithium storage performance and longer cycle life are achieved.

CN119275235BActive Publication Date: 2025-03-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411710300.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The specific capacity of the existing lithium-ion batteries is low and the cycle stability is poor, especially due to the problem of electrode powder falling off due to volume expansion during the cycle.

Method used

A negative electrode composite material is used, including graphite particles and a cladding layer coated on the surface of graphite particles. The cladding layer consists of graphene and nanosheets containing metal elements. Graphene has a network structure, and the nanosheets are embedded in the grid and come into contact with the graphite particles and are closely connected through M-O-C bonds.

Benefits of technology

It improves the embedded and disengagement of lithium ions, enhances the conductivity and cycling stability of the material, extends the service life of the battery, and maintains high-efficiency performance under high-speed charging and discharging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275235B_ABST
    Figure CN119275235B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of new energy batteries, and in particular, to a negative electrode plate, a preparation method thereof, and a battery, wherein the negative electrode plate comprises a current collector and a negative electrode active material layer disposed on the surface of the current collector, wherein the negative electrode active material layer comprises a negative electrode composite material; wherein the negative electrode composite material comprises graphite particles and a coating layer coated on the surface of the graphite particles; wherein the coating layer comprises graphene and nanosheets containing metal elements; the graphene has a mesh structure, and the mesh structure covers the outer surface of the graphite particles; the nanosheets containing metal elements are at least partially embedded in the grid of the mesh structure and contact the surface of the graphite particles. The negative electrode plate of the present invention is applied to lithium-ion batteries, which can significantly improve the specific capacity and cycle stability of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art

[0002] As a secondary battery, lithium-ion batteries mainly rely on the movement of lithium ions between the positive and negative electrodes to work. Due to their advantages such as high energy, long life, low cost, strong adaptability and environmental protection, they are widely used in energy storage power systems, power tools, portable appliances, military equipment, aerospace and other fields.

[0003] As an important component of lithium-ion batteries, the structure and performance of lithium-ion battery anode directly affect the capacity and cycle performance of lithium-ion batteries. At present, existing lithium-ion batteries generally use graphite materials as anodes. However, since the theoretical specific capacity of graphite materials is only 372mAh / g, it is difficult to meet the development needs of high-energy lithium-ion batteries. Therefore, it is urgent to develop a new high-capacity lithium-ion battery anode material.

[0004] The theoretical specific capacity of tin dioxide (SnO2) is as high as 1494mAh / g, and it is widely available, low cost and safe. Therefore, using SnO2 as the negative electrode material of lithium-ion batteries has obvious advantages. However, since SnO2 will be accompanied by huge volume expansion during the cycle (its volume expansion is greater than >300%), it is easy to cause the electrode to pulverize and fall off, resulting in a low actual capacity of lithium-ion batteries and poor cycle stability. Summary of the invention

[0005] In view of this, the present invention is committed to providing a negative electrode plate and a preparation method thereof and a battery to solve the problems of low specific capacity and poor cycle stability of lithium-ion batteries in the prior art.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector and a negative electrode active material layer disposed on the surface of the current collector, the negative electrode active material layer comprising a negative electrode composite material;

[0008] Wherein, the negative electrode composite material comprises graphite particles and a coating layer coated on the surface of the graphite particles;

[0009] Wherein, the coating layer includes graphene and nanosheets containing metal elements;

[0010] The graphene has a mesh structure, and the mesh structure covers the outer surface of the graphite particle; the nanosheet containing the metal element is at least partially embedded in the grid of the mesh structure and contacts the surface of the graphite particle.

[0011] Optionally, the nanosheets containing metal elements include at least one of SnO2 nanosheets, CuO nanosheets, Ni2O3 nanosheets and Sn nanosheets; and / or the graphene has a single-layer network structure.

[0012] Optionally, the negative electrode composite material includes MOC coordination bonds, wherein M is at least part of the metal atoms in the nanosheet containing the metal element, C is at least part of the carbon atoms in the graphite particles and / or the graphene, and O is at least part of the oxygen atoms in the nanosheet containing the metal element and / or the graphene.

[0013] Optionally, in the negative electrode composite material, the mass ratio of the graphite particles, the graphene and the nanosheets containing the metal element is (6-12): (1-2): (2-8).

[0014] Optionally, the particle size of the negative electrode composite material is 800~1000nm; and / or the particle size of the graphite particles is 300~500nm; and / or the sheet diameter of the nanosheet containing the metal element is 10~30nm; and / or the thickness of the nanosheet containing the metal element is 3~10nm.

[0015] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0016] S1, mixing graphite, a cationic surfactant and a first solvent and then performing ultrasonic treatment to obtain a first material; mixing the first material with a graphene oxide suspension and then performing stirring treatment to obtain a graphite / graphene composite material;

[0017] S2, placing a slurry containing the graphite / graphene composite material on the surface of a current collector and drying it to obtain a graphite / graphene composite electrode;

[0018] S3. Using the graphite / graphene composite electrode as a working electrode, placing the graphite / graphene composite electrode, a counter electrode and a reference electrode in an electrolyte containing target metal ions to carry out a deposition reaction.

[0019] Optionally, the cationic surfactant includes at least one of cetyltrimethylammonium bromide, cetylpyridinium chloride and cetyltrimethylammonium bromide; and / or, the first solvent includes an ethanol solution; and / or, the target metal ion includes Sn. 2+ , Cu 2+and Ni 3+ At least one of; and / or, the counter electrode is a platinum wire; and / or, the reference electrode is Ag / AgCl.

[0020] Optionally, the mass ratio of the graphite, the cationic surfactant and the first solvent is 1:0.005~0.05:10~50; and / or the mass ratio of the first material to the graphene oxide suspension is 1:0.01~0.5; and / or the pH value of the graphene oxide suspension is 8~11.

[0021] Optionally, in step S1, the conditions for the ultrasonic treatment include: a temperature of 25~40°C and a time of 90~150 min; and / or, in step S2, the conditions for the drying treatment include: a temperature of 80~120°C and a time of 4~8 h; and / or, in step S3, the conditions for the deposition treatment include: a constant current of 15~25 mA and a deposition time of 8~12 min.

[0022] A third aspect of the present invention provides a battery, characterized in that the battery comprises the above-mentioned negative electrode plate and / or the negative electrode plate prepared according to the above-mentioned method.

[0023] Through the above technical solution, the beneficial effects of the present invention are:

[0024] (1) The negative electrode plate of the present invention contains a negative electrode composite material, in which a graphene with a network structure is coated on the surface of graphite particles, providing more active sites for the embedding and extraction of lithium ions; compared with traditional layered graphite, lithium ions can be embedded in graphite / graphene in different directions, thereby improving the capacity and rate performance of graphite.

[0025] (2) The nanosheets containing metal elements in the negative electrode composite material of the present invention are at least partially embedded in the grid of the network structure. The graphene with a network structure effectively alleviates the agglomeration of the nanosheets containing metal elements and limits the volume expansion of the nanosheets containing metal elements when lithium ions are embedded, thereby improving the lithium storage performance of the nanosheets containing metal elements.

[0026] (3) In the negative electrode composite material of the present invention, the nanosheets containing metal elements and graphene are tightly connected together through MOC bonds, ensuring the stability of the structure.

[0027] (4) In the preparation method of the negative electrode plate of the present invention, a graphite / graphene oxide composite material is first synthesized, and then hydrothermal reduction is performed to prepare graphite / graphene. During the reduction process, a small portion of oxygen in the graphene oxide is not reduced. During high-temperature hydrothermal treatment, a COC bond is formed between graphite and graphene. The combination of chemical bonds can prevent the graphene layer from falling off during the insertion and extraction of lithium ions, thereby increasing the conductivity of the material and the cycle stability.

[0028] (5) The preparation process of the negative electrode sheet of the present invention is simple and easy to realize industrial production.

[0029] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0031] Figure 1 Shown is a schematic structural diagram of the negative electrode composite material of the present invention.

[0032] Figure 2 Shown is an electron microscope image of the negative electrode composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The present invention discloses a negative electrode plate and a method for preparing the same and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0034] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0035] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0039] In order to solve the problem of low specific capacity and poor cycle stability of lithium-ion batteries in the prior art, the present invention adopts the following technical solution:

[0040] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector and a negative electrode active material layer disposed on the surface of the current collector, the negative electrode active material layer comprising a negative electrode composite material;

[0041] Wherein, the negative electrode composite material comprises graphite particles and a coating layer coated on the surface of the graphite particles;

[0042] Wherein, the coating layer includes graphene and nanosheets containing metal elements;

[0043] The graphene has a mesh structure, and the mesh structure covers the outer surface of the graphite particle; the nanosheet containing the metal element is at least partially embedded in the grid of the mesh structure and contacts the surface of the graphite particle.

[0044] The schematic diagram of the structure of the negative electrode composite material in the present invention is as follows Figure 1As shown, the graphene with a mesh structure is coated on the surface of the graphite, and the three-dimensional network of graphene provides more active sites for the embedding of lithium ions, shortens the path of lithium ions embedded in the graphite, and the three-dimensional network of graphene also improves the conductivity of the overall composite material, increases the diffusion rate of lithium ions, and reduces impedance. When the negative electrode composite material of the present invention is used as the negative electrode of a lithium ion battery, the graphene with a mesh structure can provide a three-dimensional support carrier for the nanosheet containing metal elements, thereby alleviating the volume expansion of the nanosheet containing metal elements during the charging and discharging process, thereby improving the cycle stability of the lithium ion battery.

[0045] According to the present invention, the nanosheet containing metal elements may include at least one of SnO2 nanosheets, CuO nanosheets, Ni2O3 nanosheets and Sn nanosheets. Since SnO2 has smaller volume expansion, the nanosheet containing metal elements in the present invention is preferably SnO2 nanosheets.

[0046] According to the present invention, the graphene may have a single-layer mesh structure, and the graphene with the single-layer mesh structure has significantly improved flexibility and conductivity.

[0047] According to the present invention, when the nanosheets containing metal elements come into contact with the graphite / graphene surface, chemical adsorption occurs. The active oxygen atoms (O 2- ) and the metal atoms contained in the nanosheets themselves react with the oxygen atoms or carbon atoms on the graphite / graphene surface to form MOC coordination bonds and chemically bond with the graphite / graphene surface. The chemical bond connection ensures that the structure of graphite does not change when lithium ions are embedded and removed, thereby extending the cycle life of the battery. Even under high-rate charge and discharge conditions, lithium ions can be quickly embedded and removed. Wherein, M is at least part of the metal atoms in the nanosheets containing metal elements, C is at least part of the carbon atoms in the graphite particles and / or the graphene, and O is at least part of the oxygen atoms in the nanosheets containing metal elements and / or the graphene.

[0048] In the negative electrode composite material of the present invention, if the amount of nanosheets containing metal elements is too much, part of the nanosheets containing metal elements will be out of the restriction of graphene. When the battery is charged and discharged for a long time, the volume of these nanosheets containing metal elements will expand, and the pole piece will appear powder, which seriously affects the service life of the battery; if the amount of nanosheets containing metal elements is too small, it will not contribute much to improving the capacity of the anode; at the same time, if the amount of graphene is too much, single-layer graphene is prone to stacking, which reduces the channel for lithium ions to embed into graphite and reduces the capacity of the negative electrode; if the amount of graphene is too little, it is not easy to form a good conductive network with graphite, part of the graphite will be exposed, the internal resistance will increase, and the cycle performance will decrease. Exemplarily, in the negative electrode composite material, the mass ratio of the graphite particles, the graphene and the nanosheets containing metal elements can be (6~12): (1~2): (2~8).

[0049] According to the present invention, the particle size of the negative electrode composite material may be 800-1000 nm. Exemplarily, the particle size of the negative electrode composite material may be any value among 800 nm, 850 nm, 900 nm, 950 nm and 1000 nm or any value within the range of any two of the above values. In the present invention, if the particle size of the negative electrode composite material is too small, the particles of the negative electrode composite material may agglomerate during the homogenization process, thereby affecting the dispersion effect; if the particle size of the negative electrode composite material is too large, the ionic conductivity may be reduced and the rate performance may be reduced. In a preferred embodiment of the present invention, the particle size of the negative electrode composite material is 825-875 nm.

[0050] According to the present invention, the particle size of the graphite particles may be 300-500 nm. Exemplarily, the particle size of the graphite particles may be any value among 300 nm, 350 nm, 400 nm, 450 nm and 500 nm or any value within the range of any two of the above values. In the present invention, if the particle size of the graphite particles is too small, the specific capacity of the composite material may decrease; if the particle size of the graphite particles is too large, the rate performance of the material may be poor and the ionic conductivity may be poor. In a preferred embodiment of the present invention, the particle size of the graphite particles is 340-360 nm.

[0051] According to the present invention, the sheet diameter of the nanosheet containing metal elements can be 10~30nm. In the present invention, the "sheet diameter of the nanosheet containing metal elements" can be defined as the extension direction of the nanosheet containing metal elements as the radial direction, and the extension size of the nanosheet containing metal elements in the radial direction. Exemplarily, the sheet diameter of the nanosheet containing metal elements can be any value among 10nm, 15nm, 20nm, 25nm and 30nm or any value within the range value composed of any two of the above values. In the present invention, if the sheet diameter of the nanosheet containing metal elements is too small, it may lead to an increase in the specific surface area of ​​the nanosheet, a small amount of graphene, and the graphite cannot be completely wrapped, thereby affecting the conductivity of the overall material; if the sheet diameter of the nanosheet containing metal elements is too large, it may be fragile, thereby affecting the long cycle stability of the battery. In a preferred embodiment of the present invention, the sheet diameter of the nanosheet containing metal elements is 20~27nm.

[0052] According to the present invention, the thickness of the nanosheet containing metal elements can be 3~10nm. In the present invention, "the thickness of the nanosheet containing metal elements" can be defined as the dimension of the nanosheet containing metal elements perpendicular to the extension direction of the nanosheet containing metal elements as the radial direction. Exemplarily, the thickness of the nanosheet containing metal elements can be any value among 3nm, 5nm, 7nm, 9nm and 10nm or any value within the range of values ​​composed of any two of the above values. In the present invention, if the thickness of the nanosheet containing metal elements is too small, it may be fragile during the process of lithium ion insertion and extraction; if the thickness of the nanosheet containing metal elements is too large, it may not be able to completely cover the graphite. In a preferred embodiment of the present invention, the thickness of the nanosheet containing metal elements is 5~7nm.

[0053] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0054] S1, mixing graphite, a cationic surfactant and a first solvent and then performing ultrasonic treatment to obtain a first material; mixing the first material with a graphene oxide suspension and then performing stirring treatment to obtain a graphite / graphene composite material;

[0055] S2, placing a slurry containing the graphite / graphene composite material on the surface of a current collector and drying it to obtain a graphite / graphene composite electrode;

[0056] S3. Using the graphite / graphene composite electrode as a working electrode, placing the graphite / graphene composite electrode, a counter electrode and a reference electrode in an electrolyte containing target metal ions to carry out a deposition reaction.

[0057] In the process of synthesizing the graphite / graphene composite material in the present invention, the graphite / graphene oxide composite material is first synthesized, and then the graphite / graphene is prepared by hydrothermal reduction. During the reduction process, a small part of the oxygen in the graphene oxide is not reduced. During high-temperature hydrothermal treatment, COC bonds are formed between the graphite and the graphene. The combination of chemical bonds can prevent the graphene layer from falling off during the process of lithium ion insertion and extraction, thereby increasing the conductivity of the material and the cycle stability.

[0058] Exemplarily, the cationic surfactant may include at least one of cetyltrimethylammonium bromide, cetylpyridinium chloride, and cetyltrimethylammonium bromide chloride.

[0059] Exemplarily, the first solvent may include an ethanol solution.

[0060] Exemplarily, the target metal ions may include Sn 2+ , Cu 2+ and Ni 3+ At least one of .

[0061] Exemplarily, the counter electrode may be a platinum wire.

[0062] Exemplarily, the reference electrode may be Ag / AgCl.

[0063] According to the present invention, the mass ratio of the graphite, the cationic surfactant and the first solvent may be 1:0.005-0.05:10-50.

[0064] According to the present invention, the mass ratio of the first material to the graphene oxide suspension can be 1:0.01-0.5. Exemplarily, the mass ratio of the first material to the graphene oxide suspension can be any value among 1:0.01, 1:0.1, 1:0.2, 1:0.3, 1:0.4 and 1:0.5 or any value within the range of any two of the above values.

[0065] In the preparation method of the present invention, the negative electrode sheet is prepared by electrochemical deposition, wherein the graphene oxide suspension is preferably alkaline and negatively charged, and the synthetic graphite / graphene composite material also makes the graphene surface negatively charged. When the deposition reaction is carried out, it can form a MOC bond with graphite or graphene through electrostatic self-assembly. This strong chemical bond connection makes the structure of graphite unchanged when lithium ions are embedded and removed, thereby extending the cycle life of the battery. Even under high-rate charge and discharge conditions, lithium ions can be quickly embedded and removed, providing a good research basis for the study of the fast-charging performance of negative electrode materials. Exemplarily, the pH value of the graphene oxide suspension can be 8 to 11.

[0066] In the preparation process of the present invention, a graphene oxide suspension is mixed with a first material to prepare a graphite / graphene composite material, a slurry containing the graphite / graphene composite material is set on the surface of a current collector to obtain a graphite / graphene composite electrode, and in the process of a deposition reaction using the graphite / graphene composite electrode as a working electrode, target metal ions in an electrolyte containing target metal ions coordinate and bond with C atoms on the surface of graphite / graphene and oxygen atoms in graphene oxide to form MOC bonds, thereby achieving effective bonding of graphite / graphene and nanosheets of metal elements.

[0067] In one embodiment of the present invention, the preparation method of the graphene oxide suspension may include: weighing a certain amount of graphite, potassium permanganate, sodium nitrate and concentrated sulfuric acid; adding the weighed NaNO3 and concentrated sulfuric acid to a four-necked bottle in turn, placing it in an ice-water solution, and waiting for the temperature to reach about 0°C, adding the weighed graphite, stirring until the solution is uniform, and controlling the temperature to about 0°C; adding the weighed potassium permanganate to the four-necked bottle, stirring for a certain period of time, ensuring that the solution temperature is about 15°C, and observing that the solution is dark green; in a warm water bath, keeping the solution temperature at about 35°C, stirring continuously until the solution is brown-gray, adding distilled water, keeping the temperature at about 90°C, adding distilled water slowly, paying attention to the temperature change, the solution is bright yellow after adding water, and adding a certain amount of hydrogen peroxide water, filter while hot after no bubbles are generated; add the filtered cake into a large beaker, add a certain amount of concentrated hydrochloric acid and deionized water, stir to form a uniform suspension, filter, repeat several times, take a few drops of liquid, add barium chloride solution to observe whether a white precipitate is produced, if no white precipitate is produced, it means that the sulfate in the sample has been completely removed; add water to dilute the prepared sample until the pH of the graphene oxide solution reaches the pH of the washing water (exemplarily, the pH of the washing water can be 6.5-7), indicating that the solution has reached neutrality, put the prepared graphite oxide solution into a 1000mL beaker, put it into an ultrasonic cleaner for about 4 hours, stir every half an hour, and then centrifuge it in a high-speed centrifuge for 8-12 minutes, and take the supernatant as the graphene oxide suspension.

[0068] According to the present invention, in step S1, the conditions for the ultrasonic treatment may include: a temperature of 25-40° C. and a time of 90-150 min.

[0069] According to the present invention, in step S2, the drying conditions may include: a temperature of 80-120° C. and a time of 4-8 hours.

[0070] According to the present invention, in step S3, the conditions of the deposition process may include: a constant current of 15-25 mA, and a deposition time of 8-12 min.

[0071] In one embodiment of the present invention, the method for preparing a slurry containing the graphite / graphene composite material involved in the present invention may include: weighing a certain mass of graphite / graphene composite material, conductive agent and binder according to a certain mass ratio, and adding them to a small beaker in sequence. Then drip the negative electrode solvent, seal the small beaker, and stir for about 20 min. Exemplarily, the conductive agent may be at least one of acetylene black, Ketjen black, conductive graphite, graphene and carbon fiber, the binder may be polyvinylidene fluoride, and the negative electrode solvent may be N-methylpyrrolidone.

[0072] A third aspect of the present invention provides a battery, characterized in that the battery comprises the above-mentioned negative electrode plate and / or the negative electrode plate prepared according to the above-mentioned method.

[0073] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.

[0074] The present invention has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present invention can be achieved.

[0075] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.

[0076] Example 1

[0077] (1) Preparation of graphene oxide:

[0078] Weigh 7g of graphite, 30g of potassium permanganate and 7g of sodium nitrate, and measure 250mL of concentrated sulfuric acid; add the weighed NaNO3 and concentrated sulfuric acid to a four-necked bottle in turn, place it in an ice-water solution, and when the temperature reaches 2°C, add the weighed graphite, stir for 12 minutes until the solution is uniform, and control the temperature to -2°C; add the weighed potassium permanganate to the four-necked bottle, stir for 80 minutes, ensure that the solution temperature is at 12°C, and observe that the solution is dark green; in a warm water bath, keep the solution temperature at 37°C, continue stirring until the solution is brown-gray, add 650ml of distilled water, keep the temperature at 91°C, add distilled water slowly, and pay attention to the temperature change. After adding 650ml of water, the solution is bright yellow, and add 4% Hydrogen peroxide, filter while hot after no bubbles are generated; add the filtered cake into a large beaker, add a certain amount of concentrated hydrochloric acid and deionized water, stir to form a uniform suspension, filter, repeat 4 times, take a few drops of liquid, add barium chloride solution to observe whether a white precipitate is produced, if no white precipitate is produced, it means that the sulfate in the sample has been completely removed; add water to dilute the prepared sample until the pH of the graphene oxide solution reaches the pH of the washing water, indicating that the solution has reached neutrality, put the prepared graphene oxide solution into a 1000mL beaker, put it into an ultrasonic cleaner for 4h, stir every half an hour, and then centrifuge it in a high-speed centrifuge for 12min, and take the supernatant as the graphene oxide suspension (GO solution).

[0079] (2) Preparation of graphite / reduced graphene oxide:

[0080] Graphite and hexadecyltrimethylammonium bromide (CTAB) were added to a 25% alcohol solution in a mass ratio of 1:1. 50 ml of 25% alcohol solution was added to every 0.1 g of graphite, and the mixture was placed in an ultrasonic cleaner for 2 h. The pH of the GO solution was adjusted to 10 with NaOH. The GO solution was slowly added to the mixed solution of graphite and CTAB. Electrostatic self-assembly occurred during stirring, that is, the negatively charged GO and the surface-modified positively charged graphite attracted each other under the action of electrostatics to form a graphite / GO composite material. The prepared graphite / GO composite material was repeatedly rinsed with ethanol and distilled water, filtered after washing, and the filtered product was placed in a forced air drying oven at 170 ° C for 11 h. After natural cooling, the solution was taken out, filtered, and dried to obtain a graphite / rGO composite material, which was fully ground and sieved and placed in a sample bottle for later use. First, the prepared graphite / rGO composite material was sieved (300 mesh).

[0081] (3) Preparation of graphite / graphene composite electrodes

[0082] The graphite / rGO composite material, acetylene black and polyvinylidene fluoride were added to a small beaker in a mass ratio of 5:1:1, and then a few drops of N-methylpyrrolidone were added, the beaker was sealed, and stirred for 25 minutes. The slurry was then evenly coated on the copper foil using a coater, and placed in a vacuum drying oven at 110°C for 7 hours to obtain a graphite / graphene composite electrode (graphite / rGO composite electrode).

[0083] (4) Preparation of graphite / rGO / SnO2 composite electrode and negative electrode sheet:

[0084] The electrolyte was SnCl2˙2H2O aqueous solution and HNO3 aqueous solution. The sample was prepared using a three-electrode system, with a graphite / rGO composite electrode as the working electrode and a platinum wire as the counter electrode. The two electrodes were placed parallel to each other with a distance of 2 cm. The reference electrode was Ag / AgCl. Deposition was carried out under constant potential conditions with a current of 20 mA and a deposition time of 10 min to prepare a graphite / rGO / SnO2 composite electrode.

[0085] The prepared graphite / rGO / SnO2 composite electrode was punched out into a 16 mm diameter electrode sheet by a slicer, and the electrode sheet with uniform surface deposition was selected and kept at a pressure of 4 MPa for 15 s by a tablet press. Then the electrode sheet was placed in a vacuum drying oven and dried at 105°C to obtain the negative electrode sheet of this embodiment. The electron microscope image of the negative electrode composite material prepared in Example 1 is shown in FIG. Figure 2 shown.

[0086] Example 2

[0087] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Example 1, except that: 5 g of graphite, 20 g of potassium permanganate, 5 g of sodium nitrate, and 200 mL of concentrated sulfuric acid are weighed; the pH of the GO solution is adjusted to 9 with an alkaline solution such as NaOH; the current is 10 mA, and the deposition time is 10 min to prepare a graphite / rGO / SnO2 composite electrode.

[0088] Example 3

[0089] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Example 1, except that: 10 g of graphite, 40 g of potassium permanganate, 10 g of sodium nitrate, and 300 mL of concentrated sulfuric acid are weighed; the pH of the GO solution is adjusted to 11 with an alkaline solution such as NaOH; the current is 30 mA, and the deposition time is 5 min to prepare a graphite / rGO / SnO2 composite electrode.

[0090] Example 4

[0091] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that the single-layer graphene is replaced by a double-layer graphene. The specific operation is:

[0092] (1) Preparation of double-layer graphene:

[0093] First, double-layer graphene is prepared by chemical vapor deposition (CVD). Copper foil is selected as the growth substrate (copper foil has good catalytic properties, which can help the carbon source decompose and form graphene on its surface). The copper foil is cleaned (ultrasonic cleaning, the cleaning solution is DMC), and the oxides and other pollutants on its surface are removed. The cleaned copper foil is placed in the CVD reaction chamber, and the heating system is turned on to raise the substrate temperature to between 900°C and 1050°C (1000°C is used in this embodiment). This temperature range is conducive to the growth of graphene. During the heating process, protective gas (hydrogen) is introduced to exclude oxygen and other impurities. After exhausting, carbon source gas (methane) is introduced. At the same time, a certain proportion of reducing gas (hydrogen) is maintained to promote the decomposition of the carbon source; double-layer graphene is synthesized by adjusting the gas ratio, flow rate and pressure; after the growth within the predetermined time is completed, the carbon source gas is stopped, and the entire CVD device is cooled naturally. After cooling to room temperature, the reactor is opened to remove the sample. The metal substrate is etched away using an etchant (FeCl3 solution) to obtain double-layer graphene powder.

[0094] (2) Preparation of graphite / double-layer graphene:

[0095] Graphite and hexadecyltrimethylammonium bromide (CTAB) were added to a 25% alcohol solution in a mass ratio of 1:1, and 50 ml of 25% alcohol solution was added to every 0.1 g of graphite, and the solution was placed in an ultrasonic cleaner for 2 hours; the pH of the double-layer graphene solution was adjusted to 10 with NaOH; the double-layer graphene solution was slowly added to the mixed solution of graphite and CTAB; electrostatic self-assembly occurred during stirring, that is, the negatively charged double-layer graphene and the surface-modified positively charged graphite attracted each other under the action of electrostatics to form a graphite / double-layer graphene composite material; the prepared graphite / double-layer graphene composite material was repeatedly rinsed with ethanol and distilled water, filtered after washing, and dried to obtain a graphite / double-layer graphene composite material, which was fully ground and sieved and placed in a sample bottle for later use. First, the prepared graphite / double-layer graphene composite material was sieved (300 mesh).

[0096] (3) Preparation of graphite / double-layer graphene composite electrodes

[0097] The graphite / double-layer graphene composite material, acetylene black and polyvinylidene fluoride were added to a small beaker in a mass ratio of 5:1:1, and then a few drops of N-methylpyrrolidone were added, the beaker was sealed, and stirred for 25 minutes. Then, the slurry was evenly coated on the copper foil using a coater, and it was placed in a vacuum drying oven at 110°C and dried for 7 hours to obtain a graphite / double-layer graphene composite electrode.

[0098] (4) Preparation of graphite / double-layer graphene / SnO2 composite electrode and negative electrode sheet:

[0099] The electrolyte was SnCl2˙2H2O aqueous solution and HNO3 aqueous solution. The sample was prepared using a three-electrode system, with a graphite / double-layer graphene composite electrode as the working electrode and a platinum wire as the counter electrode. The two electrodes were placed parallel to each other with a distance of 2 cm. The reference electrode was Ag / AgCl. Deposition was carried out under constant potential conditions with a current of 20 mA and a deposition time of 10 min to prepare a graphite / double-layer graphene / SnO2 composite electrode.

[0100] The prepared graphite / double-layer graphene / SnO2 composite electrode was punched out into a 16 mm diameter electrode sheet by a slicer, and the electrode sheet with uniform surface deposition was selected and kept at a pressure of 4 MPa for 15 s by a tablet press. Then the electrode sheet was placed in a vacuum drying oven and dried at 105°C to obtain the negative electrode sheet of this embodiment.

[0101] Example 5

[0102] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that SnO2 is replaced by Sn single substance. The specific operation is as follows: in step (4), the electrolyte is SnCl2˙2H2O aqueous solution, HNO3 aqueous solution, the sample is prepared using a three-electrode system, with a graphite / rGO composite electrode as the working electrode, a platinum wire as the counter electrode, the two electrodes are placed parallel to each other with a distance of 2 cm, the reference electrode is Ag / AgCl, and a pulsed AC power supply is used for deposition, the current is 20 mA, and the deposition time is 10 min to prepare a graphite / rGO / Sn composite electrode.

[0103] Comparative Example 1

[0104] (1) Preparation of graphite electrode

[0105] Graphite, acetylene black and polyvinylidene fluoride were added to a small beaker in a mass ratio of 5:1:1, and then a few drops of N-methylpyrrolidone were added, the beaker was sealed, and stirred for 25 minutes. Then, the slurry was evenly coated on the copper foil using an applicator, and it was placed in a vacuum drying oven at 110°C and dried for 7 hours to obtain a graphite electrode.

[0106] (2) Preparation of graphite electrode and negative electrode sheet:

[0107] The electrolyte was SnCl2˙2H2O aqueous solution and HNO3 aqueous solution. The sample was prepared using a three-electrode system, with a graphite electrode as the working electrode and a platinum wire as the counter electrode. The two electrodes were placed parallel to each other with a distance of 2 cm. The reference electrode was Ag / AgCl. Deposition was carried out under constant potential conditions with a current of 20 mA and a deposition time of 10 min to prepare a graphite / SnO2 composite electrode.

[0108] The prepared graphite / SnO2 composite electrode was punched out into a 16 mm diameter electrode sheet by a slicer, and the electrode sheet with uniform surface deposition was selected and kept at a pressure of 4 MPa for 15 s by a tablet press. Then the electrode sheet was placed in a vacuum drying oven and dried at 105°C to obtain the negative electrode sheet of this comparative example.

[0109] Comparative Example 2

[0110] The preparation methods of graphene oxide, graphite / reduced graphene oxide and graphite / graphene composite electrodes in this embodiment are the same as those in Example 1, except that: the prepared graphite / graphene composite electrode is punched out with a 16 mm diameter electrode by a slicer, and the electrode with uniform surface deposition is selected and maintained at a pressure of 4 MPa for 15 s by a tablet press. Then the electrode is placed in a vacuum drying oven and dried at 105°C to obtain the negative electrode of this comparative example.

[0111] Test Example 1

[0112] The negative electrode composite materials in the negative electrode sheets prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were scraped and measured. The particle size of the negative electrode composite materials, the particle size of the graphite particles, the sheet size of the nanosheets containing metal elements, and the thickness of the nanosheets containing metal elements were calibrated using SEM images; the mass ratio of graphite particles, graphene oxide, and nanosheets containing metal elements (abbreviated as mass ratio in Table 1) was measured using an energy dispersive X-ray spectrometer EDS. The test results are shown in Table 1.

[0113] Table 1

[0114]

[0115] Test Example 2

[0116] The negative electrode sheets prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were assembled into CR2025 button cells. The CR2025 button cells were assembled in a high-purity argon-filled ZKX3 glove box with a moisture and oxygen concentration of less than 0.1 ppm. The counter electrode was a metal lithium sheet, the separator was a Celgard 2400 membrane (Φ19 mm), and the electrolyte solution consisted of 1M LiPF6 in ethylene carbonate / dimethyl carbonate (volume ratio 1:1).

[0117] The battery was tested for constant current charge and discharge using a NEWARE battery performance tester. The battery charge and discharge performance was tested at different current densities (0.1 A / g, 0.2 A / g, 0.5 A / g, 1.0 A / g, 0.1 A / g) within the potential range of 0.001V-3.0V. The test results are shown in Table 2.

[0118] Among them, the test method for the first discharge specific capacity is: using the Xinwei tester, the battery is charged to 3.65V at a rate of 0.5C, and then charged at a constant voltage of 3.65V to I≤0.05C, and the battery capacity is C0; the charging capacity divided by the amount of active material is the first charge specific capacity, and then discharged to 2V at a rate of 0.5C, and the released capacity divided by the amount of active material is the first discharge specific capacity C1.

[0119] The testing method for the first coulombic efficiency is: coulombic efficiency is calculated by first discharge specific capacity C1 / first charge specific capacity C0.

[0120] The test method of capacity retention rate after 200 cycles is as follows: 1. Take the battery with calibrated capacity, charge it to 3.65V at a rate of 0.5C, and then charge it to I≤0.05C at a constant voltage of 3.65V; 2. Let it stand for 30 minutes; 3. Discharge the battery to 2V at a rate of 0.5C to obtain the discharge capacity C1; let it stand for 30 minutes; repeat steps 1-3 199 times to obtain the discharge capacity C 200 ; The capacity retention rate of 200 cycles is (C 200 ) / (C1)*100% is calculated.

[0121] Table 2

[0122]

[0123] It can be seen from the data in Table 2 that the button cell assembled with the negative electrode sheet prepared in the embodiment of the present invention has better discharge specific capacity, first coulomb efficiency and cycle stability. Specifically, Example 1 has good electrochemical performance. Compared with Example 1, the parameters for preparing graphene oxide and the deposition parameters of Example 2 are adjusted. The prepared graphene oxide has a small part of agglomeration compared with Example 1. The prepared composite material has a small amount of SnO2 deposited due to the deposition current reduced from 20mA to 10mA, and there is no SnO2 on some graphite / graphene surfaces, the uniformity is poor, and the performance is reduced. In Example 3, the deposition current was changed from 20mA to 30mA, the amount of SnO2 deposited was too much, and some SnO2 nanosheets were stacked, resulting in poor cycle stability. Example 4 changes the single-layer graphene to double-layer graphene, and the pole piece becomes thicker than the single-layer graphene, which is easy to fall off and pulverize during the process of lithium ion insertion and extraction. In Example 5, SnO2 is replaced by Sn, and it is difficult to form a chemical bond between Sn and graphene, and the composite material structure is easy to collapse. Comparative Example 1 does not include graphene, and the volume expansion of SnO2 cannot be well restricted. Comparative Example 2 does not include SnO2, and the theoretical specific capacity of graphite and graphene is relatively reduced.

[0124] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active material layer disposed on the surface of the current collector, wherein the negative electrode active material layer comprises a negative electrode composite material; Wherein, the negative electrode composite material comprises graphite particles and a coating layer coated on the surface of the graphite particles; Wherein, the coating layer includes graphene and nanosheets containing metal elements; The graphene has a mesh structure, and the mesh structure covers the outer surface of the graphite particle; the nanosheet containing the metal element is at least partially embedded in the grid of the mesh structure and contacts the surface of the graphite particle.

2. The negative electrode sheet according to claim 1, characterized in that: The nanosheets containing metal elements include at least one of SnO2 nanosheets, CuO nanosheets, Ni2O3 nanosheets and Sn nanosheets; And / or, the graphene has a single-layer network structure.

3. The negative electrode sheet according to claim 1, characterized in that: The negative electrode composite material includes MOC coordination bonds, wherein M is at least part of the metal atoms in the nanosheet containing the metal element, C is at least part of the carbon atoms in the graphite particles and / or the graphene, and O is at least part of the oxygen atoms in the nanosheet containing the metal element and / or the graphene.

4. The negative electrode sheet according to claim 1, characterized in that: In the negative electrode composite material, the mass ratio of the graphite particles, the graphene and the nanosheets containing the metal element is (6-12): (1-2): (2-8).

5. The negative electrode sheet according to claim 1, characterized in that: The particle size of the negative electrode composite material is 800-1000 nm; And / or, the particle size of the graphite particles is 300-500 nm; And / or, the nanosheets containing metal elements have a sheet diameter of 10 to 30 nm; And / or, the thickness of the nanosheet containing the metal element is 3-10 nm.

6. A method for preparing a negative electrode sheet according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1, mixing graphite, a cationic surfactant and a first solvent and then performing ultrasonic treatment to obtain a first material; mixing the first material with a graphene oxide suspension and then performing stirring treatment to obtain a graphite / graphene composite material; S2, placing a slurry containing the graphite / graphene composite material on the surface of a current collector and drying it to obtain a graphite / graphene composite electrode; S3. Using the graphite / graphene composite electrode as a working electrode, placing the graphite / graphene composite electrode, a counter electrode and a reference electrode in an electrolyte containing target metal ions to carry out a deposition reaction.

7. The preparation method according to claim 6, characterized in that: The cationic surfactant comprises at least one of cetyltrimethylammonium bromide, cetylpyridinium chloride and cetyltrimethylammonium bromide; and / or, the first solvent comprises an ethanol solution; And / or, the target metal ions include Sn 2+ , Cu 2+ and Ni 3+ At least one of; And / or, the counter electrode is a platinum wire; And / or, the reference electrode is Ag / AgCl.

8. The preparation method according to claim 6, characterized in that: The mass ratio of the graphite, the cationic surfactant and the first solvent is 1:0.005-0.05:10-50; And / or, the mass ratio of the first material to the graphene oxide suspension is 1:0.01-0.5; And / or, the pH value of the graphene oxide suspension is 8-11.

9. The preparation method according to claim 6, characterized in that: In step S1, the conditions of the ultrasonic treatment include: temperature of 25-40°C and time of 90-150 min; And / or, in step S2, the drying treatment conditions include: temperature of 80-120° C. and time of 4-8 h; And / or, in step S3, the conditions of the deposition reaction include: a constant current of 15-25 mA and a deposition time of 8-12 min.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 5 and / or the negative electrode sheet prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Graphene coated graphite composite lithium ion battery negative material and its preparation method

    CN104332616A

  • Composite material and its preparation method and use in lithium ion battery

    CN108269982A